Estudio y diseño de un sistema de videovigilancia para la Facultad de la Salud Humana de la Universidad Nacional de Loja. - Arrobo Fernández, María Camila (2019)
In the study presented below, the design of a video surveillance system for the Faculty of Human Health of the National University of Loja is carried out, through which the technical criteria and requirements necessary for its future implementation are exposed, with the purpose of monitoring the administrative blocks and departments, as well as the existing equipment and implements in the faculty. This work presents an alternative from the technical point of view, to solve the problems existing in this study area, related to the loss of laboratory equipment, incidents between students, damage to physical infrastructure and the unauthorized entry of people in dependencies of restricted access. For the execution of this project, a scientific and technical framework was generated through the collection of bibliographic and normative information, which makes it possible to know each of the aspects required by the design of a video surveillance system. Following this, a visual field survey was carried out, information gathering regarding the number of students, teachers, and administrative staff; and the documentation corresponding to the total value of existing equipment and long-term assets in each block. In addition, a planimetric survey of the dimensions of the blocks was carried out, as well as the corresponding verification of the current distribution, existing in the architectural plans, provided by the Department of Physical Development of the University. Based on the aforementioned information, an analysis of architectural plans and photographic information generated from each building was developed, as well as the determination of the existing priority sites within each block, and on the exteriors of these; in order to optimize the number of raised IP cameras; and thus obtain, the largest possible coverage area, with the least amount of video devices, which avoided an excessive increase in the bandwidth required by the entire system. Likewise, the equipment available for each item was compared, with the objective of choosing, the model according to the economic and functional conditions of this project. Additionally, the integral connection of the system through fiber optic, using existing electrical poles in the faculty was considered in the design. Finally, a technical memory, network design plans and the analysis of the total cost of implementing the projected video surveillance system are generated.